The impact of next-generation sequencing in immunogenetics: current status and future directions. Issue 4 (August 2017) - Bravo-Egana, Valia; Monos, Dimitri
Abstract : Purpose of review: Next-generation sequencing (NGS) has now been established, and widely recognized, to be the preferred choice for human leukocyte antigen (HLA) typing. This transformation is based upon the many scientific, operational and economic benefits this technology affords. In this report, we review the major advantages, existing limitations and significant promise derived from adopting this technology in immunogenetics. Recent findings: Significant benefits have emerged from the usage of NGS in a relatively short period, whereby we realize that this technology not only helps addressing the technical and operational problems we have had with the legacy methods for HLA typing, but equally important, it also allows for creative applications in stem cell and organ transplantation, new ways to investigate associations of the major histocompatibility complex (MHC) with many diseases and enhance our understanding regarding the MHC and non-MHC genomic interactions. The emerging picture is one of significant benefits in the diagnostic sphere of immunogenetics and transplantation and one of interconnectivity, integrating the many biological pathways controlled and affected by this unique genomic region. Summary: NGS has revolutionized the science and practice of immunogenetics. In this article, we identify the still unresolved issues, the current benefits to transplantation and the potential for dissecting the complexity of the MHC, one of the most fascinating regions of the human genome. Using current trends, an attempt is made to predict future directions and outcomes.